Pengetahuan Etnobotani Suku Manggarai dan Implikasinya Terhadap Pemanfaatan Tumbuhan Hutan di Pegunungan Ruteng - Elisa Iswandono; Ervizal Amir Muhammad Zuhud; Agus Hikmat; Nandi Kosmaryandi (Institut Pertanian Bogor, 2015)
Ruteng mountains are inhabited by the tribe Manggarai. Local community in the mountains of Ruteng have ethnobotany knowledge in utilization forest plant to meet their needs. Loss of traditional knowledge would have negative impacts on forest resources, because the indigenous people would have less knowledge on sustainable ways to manage the existing forest resources so that a research is required to identify the status of traditional knowledge. This study aims to analyze the level of knowledge of ethnobotany, retention rate, and the rate of change of the annual retention on the indigenous people in the Ruteng mountains. The research was conducted in the Kampung Mano, Lerang, and Wae Rebo, Manggarai District within the Province of Nusa Tenggara Timur in the period of July-December 2014. Data was obtained through Focus Group Discussion (FGD), semi-structured interviews with 90 respondent, and in-depth interviews. Data obtained were analyzed for the level of ethnobotany knowledge, ethnobotany retention index, and testing the significance of the factors that affect the level of knowledge with Kruskal Wallis test and Man Whitney. The results of the study shows that the Manggarai communities in the Mountains of Ruteng have local knowledge to meet daily needs, especially food, and medicine through the utilization of forest plant. The level of ethnobotany knowledge is high because they use forest plants, practice traditional rituals, and inheritance knowledge. The ethnobotany knowledge of young generation decreased which can give negatif impact to forest conservation.